Effect of center of rotation of angulation‐based leveling osteotomy on ex vivo stifle joint stability following cranial cruciate ligament transection and medial meniscal release with and without a hamstring load. Issue 6 (15th March 2022) - Mazdarani, Parisa; Pedram, Mir Sepehr; Miles, James E.
Abstract: Objective: To evaluate the effect of center of rotation of angulation (CORA)‐based leveling osteotomy (CBLO) and hamstring load on stifle stability following cranial cruciate ligament transection (CCLx) and medial meniscal release (MMR). Study design: Ex vivo experimental study. Sample population: Cadaver hind limb preparations ( n = 7). Methods: After instrumentation, constant quadriceps and gastrocnemius loads with an optional hamstring load in a 3:1:0.6 ratio were applied, and stifles were extended from fully flexed using an electrical motor during fluoroscopic recording. The recording process was repeated after each of CCLx, MMR and CBLO and the extracted landmark coordinates were used for calculation of cranial tibial translation (CTT) and patellar ligament angle (PTA). Results: Mean initial tibial plateau angle was 28.1°: post‐CBLO the mean was 9.7°. Cranial tibial translation developed from 50° and 75° with CCLx and MMR respectively ( p < .04, < .02) without hamstring loading. Hamstring loading mitigated CTT due to CCLx and delayed CTT until 120° for MMR ( P < .02) in this model. CBLO prevented CTT, except at 140° without hamstring loading ( P = .01). Similar results were seen for PTA, but CBLO curves were parallel to and lower than intact values at all tested angles ( P < .04), consistent with induced effective joint flexion. Conclusion: CBLO to a target tibial plateau angle of 10° largely eliminated CTT induced by CCLx and MMR. Hamstring loads of 20% quadriceps load improved stifle stability in this model. Impact: Stifle stability following CBLO appears to be multifactorial and depends on meniscal integrity, joint angle, and hamstring strength.